Meningkatkan Kesadaran Masyarakat Untuk Memberdayakan Diri Di Era Covid-19 Di Kecamatan Tongas Kabupaten ProbolinggoMeningkatkan Kesadaran Masyarakat Untuk Memberdayakan Diri Di Era Covid-19 Di Kecamatan Tongas Kabupaten Probolinggo - Dita Tia Mukarromah; Verto Septiandika (Abdi Panca Marga, 2021)
COVID-19 virus has caused the world to experience a pandemic, as a result of which many countries have experienced disruptions in almost all sectors, including the health, economic and education sectors. In Indonesia , the spread of the Covid-19 virus is quite worrying, because every last update in February 2021 the spread of the Covid-19 virus can reach 10,000 cases every day. the spread of the Covid-19 virus, the government urges all people to apply a new lifestyle, namely 3M (Wearing masks, Washing hands, Maintaining distance). To support from the government regarding the prevention of Covid 19, the KKN University of Panca Marga Probolinggo 2021 held a community service work program related to education on the dangers of Covid and its prevention, especially in the Tongas District, Probolinggo Regency. Based on the identification of problems, the service program focuses on: 1) Guidance for students affected by Covid 19, 2) Socialization of the importance of preventing stunting in improving community welfare during the Covid 19 pandemic 3) distributing Personal Protective Equipment (PPE), 4) Guiding UMKM in development of new product innovations. This is three methods used, namely the education method, the socialization method, and evaluation program. The data collection method in this program uses interview techniques, documentation and questionnaire. In addition to assisting the government in suppressing the rate of spread COVID-19, the objective of these programs is to increase public awareness in implementing healty lifestyle in the pandemic COVID-19 . Keywords: Covid-19 spread ; Covid-19 Prevention; Community Service.